Dietary Regulation As A Factor Predicting Quality of Life in Diabetic Peripheral Neuropathy Patients - Ritonga, Sukhri Herianto; Decroli, Eva; Prahastuti, Brian Sri; Usman, Elly; Mudjiran, Mudjiran; Bachtiar, Adang; Afriwardi, Afriwardi; Yetti, Husna (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Diabetic peripheral neuropathy is a complication of diabetes mellitus with the number of sufferers continuing to increase from time to time. A decrease in quality of life occurs as this disease progresses, both in physical, mental, and social aspects. Controlling risk factors for declining quality of life needs to be done early, one of the risk factors for declining quality of life is diet. The aim of this research is to analyze dietary regulation as a predictive factor for quality of life in diabetic peripheral neuropathy sufferers. The type of research used is quantitative research with a cross-sectional approach. The respondents in the study were 210 diabetic peripheral neuropathy sufferers who were selected using consecutive sampling techniques. Data collection uses a questionnaire that meets the existing validity and reliability criteria. The data analysis used in this research is SEM PLS analysis. The results show that dietary regulation has a positive influence on quality of life (r=0.236, p=0.0001). Dietary regulation has an effect size on quality of life (f square = 0.095) and also has the ability to predict quality of life well (Q square = 0.232). Dietary regulation is also feasible and suitable in explaining interactions between variables (NFI = 0.540; SRMR = 0.99). The conclusion is dietary regulation can be a good predictive factor for quality of life, so that by improving the diet of diabetic peripheral neuropathy sufferers it will be possible to improve their quality of life.